EMPLOYEE PERFORMANCE AFFECTED BY WORKLOAD, WORK MOTIVATION, AND SUPPORT MANAGEMENT - Akhmad Nurrofi; Sri Sulistyoningsih (Jurnal Scientia, 2022)
The purpose of this research is to explain the relationship between workload, work motivation, and management support to improve employee performance. In this study using a questionnaire with a scale of 1-5 and sampling using a census with a sample of 35 respondents. The data obtained was then analyzed using the SPSS version 21 program. The results of statistical tests concluded that (1) there is no positive and significant influence between workload on employee performance, (2) there is a positive and significant influence on work motivation on employee performance, (3) there is a positive and significant influence on Management Encouragement on performance employees, which means how much workload given to employees will not affect employee performance. The better the employee's work motivation, the higher the employee's performance. The better the management's encouragement.